Kajian Stilistika dalam Lagu Happy Asmara Wis Tatas - Natalia, Kristin (Kaloka Jurnal Pendidikan Bahasa dan Sastra Daerah, 2023)
The lyrics of this song are the lyrics of a dangdut song performed by Happy Asmara in Javanese. The interesting thing to study further is the use of diction and the theme using stylistics, namely looking at the style of language used. Stylistic studies are directed to discuss the content of literary works. In general, stylistic studies include diction or word choice (lexical choice), sentence structure, figure of speech, partnership, rhyme patterns, and dimensions used by the author or contained in literary works. This study aims to analyze the use of diction and themes contained in the lyrics of the Dangdut Happy Asmara song entitled "Wis Tatas". The method used is the library method because the object is the text of the song lyrics. Like the style chosen by the author, stylistic theory is used, which does not see aesthetics in song lyrics. The end of this method is the result of the data analysis presentation. The presentation of the results of data analysis begins with the presentation of diction on the data sources contained in the lyrics of the song Happy Asmara. Then proceed with an explanation of the theme of the lyrics. The results of the research found are that in the lyrics of the song Happy Asmara, the figure of speech used is the simile. In addition, the lyrics of the song Happy Asmara use non-majas. Non-majors used consist of repetition, inversion, and rhetoric. Happy Asmara's song lyrics also contain diction consisting of empty symbols, natural symbols, and special symbols. Happy Asmara song lyrics also contain pictures or images. The image or image contained in the lyrics of the song Happy Asmara consists of visual imagery (visual), auditive imagery (hearing), tactical imagery (touching), and gustative imagery (touch). The theme contained in the lyrics of the song Happy Asmara consists of a chorus.